2015
DOI: 10.1016/j.psep.2014.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Optimization procedure to select an inherently safer design scheme

Abstract: There are different well-established strategies for making a process plant inherently safer. The benefits of applying these strategies on reducing the overall risk inside a plant are obvious.However, some of these changes are rejected many times because they appear to be too costly.But if the effects of applying inherently safer design strategies are investigated not only on the processing costs of a plant but also on the potential accident costs, the decision would in fact be different. In this paper an optim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…10 inherent safety strategies are incorporated into the optimization algorithm by considering 184 decision parameters associated with each strategy. The novelties of the present study in 185 comparison to the previous research(Eini et al, 2015) are as follows: 186  Multi-objective optimization programming is applied in order to simultaneously optimize 187 economics as well as inherent safety measures 188 Detailed quantitative risk assessment is applied in order to measure inherent safety 189 considering incidents frequencies and consequences 190  The combination nature of accident scenarios is formulated in the optimization program.191  Layout optimization considering land cost in the economic analysis as well as safe 192 distances in the case study 193 Accidents frequencies have not been considered in the procedure presented by Eini et al (2015). 194 Their defined objective function comprised of summing plant processing costs and accident 195 costs.…”
mentioning
confidence: 75%
See 4 more Smart Citations
“…10 inherent safety strategies are incorporated into the optimization algorithm by considering 184 decision parameters associated with each strategy. The novelties of the present study in 185 comparison to the previous research(Eini et al, 2015) are as follows: 186  Multi-objective optimization programming is applied in order to simultaneously optimize 187 economics as well as inherent safety measures 188 Detailed quantitative risk assessment is applied in order to measure inherent safety 189 considering incidents frequencies and consequences 190  The combination nature of accident scenarios is formulated in the optimization program.191  Layout optimization considering land cost in the economic analysis as well as safe 192 distances in the case study 193 Accidents frequencies have not been considered in the procedure presented by Eini et al (2015). 194 Their defined objective function comprised of summing plant processing costs and accident 195 costs.…”
mentioning
confidence: 75%
“…The value of optimization variables for the base case design (Figure 4), P=676 kPa, NPP=1), the 639 solution reported by Eini et al (2015) (P= 600kPa, NPP= 11), and the optimum solution found in 640 this study (P= 350 kPa, NPP= 6) are shown in Table 6. Table 6 suggests that, in comparison to 641 the base-case, for 19 percent increase in the TAC, it is possible to increase the level of process 642 safety by 1 order of magnitude.…”
mentioning
confidence: 89%
See 3 more Smart Citations